Dye-sensitized solar cells based on Fe N-heterocyclic carbene photosensitizers with improved rod-like push-pull functionality. Issue 48 (1st December 2021) - Lindh, Linnea; Gordivska, Olga; Persson, Samuel; Michaels, Hannes; Fan, Hao; Chábera, Pavel; Rosemann, Nils W.; Gupta, Arvind Kumar; Benesperi, Iacopo; Uhlig, Jens; Prakash, Om; Sheibani, Esmaeil; et al.
Abstract : Iron-based photosensitizers for dye-sensitized solar cells with a rod-like push–pull design. Solar cell performance was limited by ultrafast (sub-ps) recombination, but yielded better performance than the homoleptic parent photosensitizer. Abstract : A new generation of octahedral iron(ii )–N-heterocyclic carbene (NHC) complexes, employing different tridentate C^N^C ligands, has been designed and synthesized as earth-abundant photosensitizers for dye sensitized solar cells (DSSCs) and related solar energy conversion applications. This work introduces a linearly aligned push–pull design principle that reaches from the ligand having nitrogen-based electron donors, over the Fe(ii ) centre, to the ligand having an electron withdrawing carboxylic acid anchor group. A combination of spectroscopy, electrochemistry, and quantum chemical calculations demonstrate the improved molecular excited state properties in terms of a broader absorption spectrum compared to the reference complex, as well as directional charge-transfer displacement of the lowest excited state towards the semiconductor substrate in accordance with the push–pull design. Prototype DSSCs based on one of the new Fe NHC photosensitizers demonstrate a power conversion efficiency exceeding 1% already for a basic DSSC set-up using only the I − /I3 − redox mediator and standard operating conditions, outcompeting the corresponding DSSC based on the homoleptic reference complex. Transient photovoltage measurements confirmed that adding the co-sensitizer chenodeoxycholic acid helped in improving the efficiency by increasing the electron lifetime in TiO2 . Time-resolved spectroscopy revealed spectral signatures for successful ultrafast (<100 fs) interfacial electron injection from the heteroleptic dyes to TiO2 . However, an ultrafast recombination process results in undesirable fast charge recombination from TiO2 back to the oxidized dye, leaving only 5–10% of the initially excited dyes available to contribute to a current in the DSSC. On slower timescales, time-resolved spectroscopy also found that the recombination dynamics (longer than 40 μs) were significantly slower than the regeneration of the oxidized dye by the redox mediator (6–8 μs). Therefore it is the ultrafast recombination down to fs-timescales, between the oxidized dye and the injected electron, that remains as one of the main bottlenecks to be targeted for achieving further improved solar energy conversion efficiencies in future work.